مدى تأثير الاتمتة الذكية على مستقبل وظيفة المراجع الداخلي والخارجي (دراسة نظرية تحليلية) - سماح منصور صوان; عدنان عياد الغليظ (Surman Journal of Science and Technology, 2026)
Focusing on the opportunities and risks associated with intelligent automation in the auditing sector, this study sought to determine how intelligent automation will affect the future of internal and external auditing professions in Libya. Employing a descriptive-analytical approach with a forward-looking perspective, the study concluded that intelligent automation has changed the nature of auditors’ work by increasing the focus on analytical and advisory tasks and reducing reliance on traditional routine activities. Technologies such as artificial intelligence (AI) and big data analytics have helped accelerate audit procedures while improving their accuracy and efficiency. Auditors must acquire technical skills such as information security, data analysis, and AI systems management to keep pace with these developments. The results also showed that intelligent automation has transformed the auditor’s work, making it more strategic and reliant on smart technology to identify errors and risks, impacting the job market and creating a greater need for auditors with technical and analytical skills. The study also revealed ethical and technological challenges related to information security and data protection, necessitating the development of appropriate legislation. The study concluded with several important recommendations, including educating auditors about automation and AI, reconsidering their work to be more strategic, and integrating Smart auditing in risk management, the application of rigorous data protection guidelines, and close monitoring of artificial intelligence developments ensure a positive and lasting impact on auditors’ career paths.